Premutations in C9ORF72 and FMR1 in Iceland - Ástrós Skúladóttir 1991- (2019)
Modern sequencing technology has been instrumental in determining the sequence of DNA. However, there are regions within the genome that cannot be sequenced using traditional methods. Repetitive DNA sequences such as GC-rich repeat expansions can alter gene expression and confer risk of or cause diseases. If these repeats are not fully expanded, they are sometimes called premutations (PM). PM may contribute to neuropsychological and/or neurodegenerative disorders and can mutate to a full mutation (FM). Attaining the number of long repeats has been problematic, especially for a large population based sample. Here, we used a novel approach involving whole genome sequencing, two-primer PCR, and three-primer PCR to determine accurately the repeat number in C9ORF72. We used genotype data together with data from a three-primer PCR to find PM haplotypes in FMR1 and used them to identify PM candidates in the Icelandic population. The varying lengths of the C9ORF72 and FMR1 repeats were then associated with different phenotypes. We detected a significant association between long repeats in C9ORF72 and ALS (p = 5.14×10-7, OR = 86.4). Further, we detected an association with Alzheimer’s disease (p = 5.09×10-5, OR = 16.1). Phenotypes previously associated with the FMR1 PM could not be confirmed in the Icelandic sample. The novel approach used in this study can be used to identify PM carriers of other repeat expansions and estimate their impact in large samples. Raðgreiningartækni hefur spilað mikilvægt hlutverk í að ákvarða röð niturbasanna í erfðamengi mannsins. Það eru þó svæði innan þess sem er ekki hægt að raðgreina með hefðbundnum aðferðum. Langar og GC-ríkar endurtekningar í erfðamenginu eru dæmi um svæði sem erfitt er að raðgreina en slíkar raðir geta breytt tjáningu gena og valdið sjúkdómum. Til eru endurtekningar sem kallast forstökkbreytingar (PM) en þær eru ekki jafn langar og sjúkdómsvaldandi endurtekningar (FM) en geta þó aukið líkur á öðrum röskunum í taugakerfinu. Það hefur verið erfitt að leggja mat á ...